Parent-set bedtime in adolescence is associated with future cardiovascular disease risk: Evidence from the Add Health study - Prince Nii Ossah Addo; Angela D. Liese; Jiajia Zhang; Glenn Weaver; Monique J. Brown (PLoS ONE, 2025)
Parent-set bedtimes have been linked to a lower prevalence of key cardiovascular disease (CVD) risk factors in adolescents. However, little is known about how parent-set bedtimes during adolescence affect CVD risk later in life. This study examined the association between parent-set bedtimes and future CVD risk, as well as the potential mediating role of sleep health. Data were taken from Waves I and IV of the National Longitudinal Study of Adolescent to Adult Health, including 4,151 participants. Parent-set bedtimes (10:00 PM, by 11:00 PM, and by midnight) were collected at Wave I. The outcome measure was the 30-year Framingham CVD score, categorized as low or high risk. Analyses were performed using SURVEYLOGISTIC and CAUSALMED procedures in SAS. About 28% of adolescents had a parent-set bedtime by or after 11 PM, while 18% had no parent-set bedtime. Adolescents with parent-set bedtimes by or after midnight (aOR: 2.32, 95% CI: 1.65–3.26) and those without a parent-set bedtime (aOR: 1.35, 95% CI: 1.01–1.79) had significantly higher CVD risk in adulthood compared to those with earlier bedtimes (by 10 PM). Sleep health partially mediated the relationship between parent-set bedtime and future CVD risk. Our study findings indicate that parental-set bedtimes during adolescence are associated with future CVD risk. Further prospective or experimental studies are needed to confirm these relationships.